Bamboo partition / Muhamad Shalihin Mat Dom - Mat Dom, Muhamad Shalihin (Faculty of Applied Sciences, 2016)
The product is important for element of economic improvement in developing countries. It focuses interior, and also offer a higher look and additional valuable in the market and the suitability of material for produced bamboo partition using a simple design. The wall partition was produced, and the data were collected via survey form. The data were analyzed using SPSS based on questionnaire that had been distributed to 100 correspondents. 80% of the correspondents give positive response to the material used, suitable furniture. portable, simple design and price. From this study it can be concluded that bamboo partition can be accepted by all age level, gender and also a profession. Most of correspondent agreed that partition made by bamboo give the traditional view. Most of the correspondents agreed for this product that can give good advantages for furniture industry.